KAJIAN MOLEKULER RESISTENSI Candida albicans TERHADAP ANTIFUNGI - Damiana Sapta Candrasari (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2014)
Abstract: Candida albicans is one of the species Candida which mostly cause infection inhuman. Antifungal agent azole, polyene, echinocandin, and flucytosine are commonly used forCandida albicans infection treatment. The increasing using antifungal agent will causeantifungal resistance. Most of this resistance happen through gene mutation. This mutationmay influence efflux pumps, interaction of the drug and the target enzyme, the component offungal structure biosynthesis, and conformation of compound in fungal cell.Keywords: Candida albicans, antifungal agent, resistance, gene mutation